Frequency, geographical distribution, clinical characteristics, antivenom utilisation and outcomes of King Cobra (Ophiophagus hannah) bites in Malaysia. - Asyhok Renault; Vera Effa Rezar Frederic Ng; Wan Chee Goh; Muhammad Nadzmi Hadi Abd Hamid; Annuar Muhammad Zuljamal Osman; Ruth Sabrina Safferi; Zainalabidin Mohamed Ismail; Ahmad Khaldun Ismail (Public Library of Science (PLoS), 2024)
Snakebite envenomation remains an important, yet a neglected public health issue in most tropical and subtropical countries. Underdeveloped medical infrastructure, suboptimal medical services, poor documentation and failure to make snake-related injury a mandatory notifiable disease are important contributing factors. The King Cobra (Ophiophagus hannah) is a medically significant species encountered in Malaysia however, there have been few publications from the clinical perspective. The objectives of this study were to determine the frequency of King Cobra related injuries, geographical distribution, clinical presentation, type and frequency of antivenom utilization and the management outcome. This is a cross-sectional study of confirmed King Cobra related injuries consulted to Remote Envenomation Consultation Services (RECS) from 2015 to 2020. Data were extracted from the RECS database and descriptively analyzed. A total of 32 cases of King Cobra bite were identified. Most cases were from Peninsular Malaysia with the most frequent from the state of Pahang (n = 9, 28.1%). Most patients got bitten while attempting to catch or play with the snake (68.8%). Signs and symptoms of envenomation were documented in 24 (75.0%) cases and the most frequent systemic manifestation was ptosis (n = 13, 40.6%). Tracheal intubation and ventilatory support were required in 13 (40.6%) patients. Antivenom was administered to 22 (68.8%) patients with most (25.0%) receiving 10 vials (1 dose). The commonest antivenom used was monospecific King Cobra antivenom (50.0%) from Thai Red Cross. There was one death documented due to complications from necrotizing fasciitis and septicemia. Public awareness of the dangers and proper handling of King Cobras needs to be emphasised. Timely administration of the appropriate antivenom is the definitive treatment and leads to favorable outcomes.